Effects of nano-scale nutrients supplement on natural productivity of Thalassiosira sp. and growth performance of Pacific white shrimp, Litopenaeus vannamei, reared under intensive conditions using concrete tank culture system - Novriadi, Romi; Fadhilah, Rifqi; Eka Wahyudi, Aldy; Prayogi, Dea Ananda; Ilham, Ilham; Nanda, Sunil (Jurnal Akuakultur Indonesia, 2021)
ABSTRACT The aim of this study was to evaluate the use of unique mixture of nano-nutrient to extent the growth of diatom Thalassiosira sp. and the effect to the water quality, growth performance, and protein composition on the whole body of the Pacific white shrimp Litopenaeus vannamei. There are four treatments with four replicates per treatment with the use of commercial nano-nutrients (Aquaritin Aquaculture or AA) namely: (1) 0.70 mg/L; (2) 0.525 mg/L, (3) 0.35 mg/L, and (4) without any AA application, but included standard application of using urea and NPK fertilizers to enhance the growth of diatom. The use of AA was successful to trigger the growth of Thalassiosira sp. Group of shrimp treated with 0.70 mg/L had better growth rate. Results of feeding trial indicated that adding AA could also improve the biomass, final mean weight, survival, percentage weight gain, and better feed utilization in terms of FCR. The addition of AA to enhance the growth of Thalassiosira sp. also provides a beneficial impact to the protein composition in whole body of shrimp. Biologically, the protein composition in the whole body of shrimp treated with 0.7 mg/L was higher. The findings from this study showed that the addition of commercial nano-nutrient could enhance the growth of Thalassiosira sp. and led to better growth of shrimp cultured in concrete tank Key words: Growth, Litopenaeus vannamei, nano-nutrients, protein composition, Thalassiosira sp. ABSTRAK Tujuan penelitian yaitu mengevalusi penggunaan campuran unik nano-nutrien untuk meningkatkan pertumbuhan diatom Thalassiosira sp. dan pengaruhnya terhadap kualitas air, laju pertumbuhan, dan komposisi protein pada tubuh udang L. vannamei. Terdapat empat perlakuan dan empat ulangan per perlakuan dengan penggunaan nano-nutrisi komersial (Aquaritin Aquaculture atau AA) yaitu: (1) 0,70 mg/L; (2) 0,525 mg/L; (3) 0,35 mg/L, dan (4) tanpa pemberian AA, tetapi menggunakan penerapan standar pupuk urea dan NPK untuk pertumbuhan diatom. Penggunaan AA berhasil memicu pertumbuhan Thalassiosira sp. Kelompok udang yang diberi perlakuan 0,70 mg/L memiliki laju pertumbuhan yang lebih baik. Hasil uji coba pemberian pakan menunjukkan bahwa penambahan AA juga dapat meningkatkan biomassa, bobot rata-rata akhir, kelangsungan hidup, persentase pertambahan bobot dan pemanfaatan pakan yang lebih baik dalam hal FCR. Penambahan AA untuk meningkatkan pertumbuhan Thalassiosira sp. juga memberikan dampak yang menguntungkan bagi komposisi protein di seluruh tubuh udang. Secara biologis komposisi protein di tubuh udang dengan perlakuan 0,70 mg/L lebih tinggi. Hasil dari kajian ini menunjukkan bahwa penambahan nano-nutrien komersial dapat meningkatkan pertumbuhan Thalassiosira sp. dan mendorong pertumbuhan udang bada sistem budidaya di bak beton. Kata kunci: Komposisi protein, Litopenaeus vannamei, nano-nutrien, pertumbuhan, Thalassiosira sp.